Metastatic Cancer of Cowper's Gland: A Rare Cancer Managed Successfully by Molecular Profiling - Myers, Charles E. (S. Karger AG, 2014)
Cancer of Cowper's gland is a very rare cancer. This case represents the 9th case in the medical literature. As such, there are no phase II or phase III trials to guide treatment. In this article, we report the successful treatment of a patient over a 7-year period guided solely by molecular profiling. Through multiple cycles to treatment, the cancer was controlled using drugs targeting c-kit, as the cancer steadily increased the expression of c-kit. This report also documents the use of a novel drug combination based on sunitinib that was well tolerated and may warrant testing in other c-kit-dependent cancers.